Beyond Killing Mycobacterium tuberculosis: Disease Tolerance - Divangahi, Maziar; Khan, Nargis; Kaufmann, Eva (Frontiers in Immunology, 2018)
Host defense strategies against infectious diseases are comprised of both host resistance and disease tolerance. Resistance is the ability of the host to prevent invasion or to eliminate the pathogen, while disease tolerance is defined by limiting the collateral tissue damage caused by the pathogen and/or the immune response without exerting direct effects on pathogen growth. Our incomplete understanding of host immunity against tuberculosis (TB) is predominately rooted in our bias towards investigating host resistance. Thus, we must refocus our efforts to understand the entire spectrum of immunity against M. tuberculosis to control TB.